Von Willebrand Factor Propeptide in Vascular Disorders - van Mourik, Jan A.; Wit, Thalia Romani de (Thrombosis and Haemostasis, 2001)
Von Willebrand factor (VWF) is a multifunctional plasma protein that plays a prominent role in haemostasis. In endothelial cells, processing of its precursor pro-VWF results in the formation of two large polypeptides, mature VWF and a propeptide. These proteins are co-secreted on an equimolar basis but are cleared from the circulation at different rates. VWF levels are frequently elevated in response to vascular disorders. Similarly, propeptide levels are increased under these conditions, although primarily in fulminant vascular disease, such as thrombotic thrombocytopenic purpura and septicemia. In chronic vascular disease, e.g. diabetes or peripheral vascular disease, propeptide levels are much less elevated. The differential response of VWF and propeptide levels to vascular disease could provide a means to assess the extent and time course of endothelial cell activation. After secretion, the propeptide may play a role in modulating cellular adhesion processes. Thus, enhanced propeptide secretion seems not to be of merely diagnostic significance.
Keywords: Von Willebrand factor; endothelial cells; von Willebrand factor propeptide; vascular disease; Weibel-Palade bodies